Is the Action or Discourse of the Central Bank of the Republic of Türkiye More Effective on Expected Inflation? - Tufaner, Mustafa Batuhan; Köse, Nezir; Süt, Ali Talih (Panoeconomicus, 2025)
This study examines the effects of central bank discourse (tone index), action (policy rate), and actual inflation on expected inflation for Türkiye using monthly data between 2020 and 2024 via the SVAR model. Empirical findings demonstrate that the tone index has a statistically significant negative effect on expected inflation for one month, while actual inflation has a statistically positive effect for two months. These results suggest that the CBRT’s discourse, rather than its action, has a greater impact on expected inflation in the short term. In addition, the findings indicate that actual inflation has a significant impact on expected inflation in the short run. JEL: C32, E52, E58